Paul, Pagans and Eschatological Ethnicities A Response to Denys McDonald - Fredriksen, Paula 1951-; McDonald, Denys N. (2022)
An invited response to Denys McDonald’s JSNT essay: ‘“Ex-Pagan Pagans”? Paul, Philo, and Gentile Ethnic Reconfiguration’.